Farm Telecast Viewing Behaviour of Farmers - Shahila Rose J S (Department of Agricultural extension, College of Agriculture, 1990)
This study entitled “Farm Telecast Viewing Behaviour of Farmers” was carried out in Nedumangadu Taluk of Trivandrum district with the following objectives: